Zamala wrote:
I agree with Runnyboy44's doubts about the answer. How are we supposed to know that we do not have to consider the case - -(|-3|) = +3 in this case?
This doubt could be corroborated by looking at exercises where the function is defined as a # b = (+)|a + b|. Then I would seperate between case 1:
a # b = (+)|a + b|
and case 2: a # b = (-)|a + b|
.
how are we supposed to that we should limit our answer strategy to plugging in.
Hi..
we have to just read the information given in the question while we solve a question.
The question gives us a function a # b = (-)|a + b|...
Now you have to find (-10)#7, this means a=-10 and b=7, so substitute in the function to get (-10)#7=-|-10+7|=-3
|a|=-a when a<0.. But this is true when you do not know the value of a. Here you know what a and b stands for..
Even here a+b=-10+7=-3<0 so |a+b|=-(a+b) when (a+b)<0 thus |-10+7|=-(-10+7)=-(-3)=3..
But we are looking for -(|a+b|), which will be equal to -(3)